PANDANGAN TOKOH PESANTREN TERHADAP EKSISTENSI ULAMA PEREMPUAN DI KABUPATEN ACEH BARAT - IRMA JURAIDA (Jurnal Community, 2016)
This study discusses about Islamic figures boarding point of view toward “ulama” woman figure existence in West Aceh Regency. “The problem of the study of this thesis is analysis about how is point of view of social about existence.. This research is done in West Aceh Regency by using qualitative approach, especially by a much deeper interview technique method by meeting directly and observation. “Ulama” woman figure point of view is assumed as dialectic process (habitus, capital and field) and by time journey (history process and usuality) and influence by social environment (domain) that creating it. The result of this study shows that social point of view about existence “Ulama” woman figure is more fix by usuality, social background, culture and religious value that is comprehended by Islamic figures boarding or people or society group pertinent as a “Ulama” man figures friends and still contribution in woman capacity (taklim, local preachers, teachers or recitation teungku). Key words: social view, Islamic figures boarding, existences “Ulama” woman figures